Prevalencia de Staphylococcus aureus meticilino resistente (SARM) presentes en pacientes poli traumatizados en una clínica privada de la ciudad de Montería entre los años 2017 a 2019 (2020)
Objective. To determine the prevalence of resistant methicillin-resistant Staphylococcus aureus (MRSA) present in polytraumatized patients in a private clinic in the city of Montería, during the years 2017, 2018 and 2019. Materials and methods. A retrospective descriptive study was carried out in a private clinic in the city of Montería where the databases of the area corresponding to microbiology were analyzed, specifically the admitted positive patients for the isolation of Staphylococcus aureus. Population: it consisted of 1,674 polytraumatized patients admitted to the different clinical services of a private clinic in the city of Montería between the years 2017 to 2019. The variables that were taken into account for the statistical analysis were: Isolated microorganism, origin of the sample, isolation service and susceptibility profile. Results. During the years 2017 to 2019 the clinic hospitalized 16,541 patients, of which 1,674 were polytrauma patients where a total of 46 samples from different anatomical sites positive for MRSA were isolated, with wound secretions and bone infections being the most they were associated with bacterium infections. Conclusions Hospitalized patients belonged in a higher percentage to the male sex, possibly due to their type of occupation. The clinical service with the highest number of MRSA isolates was the ICU, a fact that is possibly related to the severity of the injury.